Capsaicin Potentiates Anticancer Drug Efficacy Through Autophagy-Mediated Ribophorin II Downregulation and Necroptosis in Oral Squamous Cell Carcinoma Cells - Huang, Yi-Ching; Yuan, Tien-Ming; Liu, Bang-Hung; Liu, Kai-Li; Wung, Chiung-Hua; Chuang, Show-Mei (Frontiers in Pharmacology, 2021)
The ability of capsaicin co-treatment to sensitize cancer cells to anticancer drugs has been widely documented, but the detailed underlying mechanisms remain unknown. In addition, the role of ribophorin II turnover on chcemosensitization is still uncertain. Here, we investigated capsaicin-induced sensitization to chemotherapeutic agents in the human oral squamous carcinoma cell lines, HASC-3 and SAS. We found that capsaicin (200 M) did not induce remarkable apoptotic cell death in these cell lines; instead, it significantly enhanced autophagy with a concomitant decrease of ribophorin II protein. This capsaicin-induced decrease in ribophorin II was intensified by the autophagy inducer, rapamycin, but attenuated by the autophagy inhibitors, ULK1 inhibitor and chloroquine, indicating that the autophagic process was responsible for the capsaicin-induced down-regulation of ribophorin II. Co-administration of capsaicin with conventional anticancer agents did, indeed, sensitize the cancer cells to these agents. In co-treated cells, the induction of apoptosis was significantly reduced and the levels of the necroptosis markers, phospho-MLKL and phospho-RIP3, were increased relative to the levels seen in capsaicin treatment alone. The levels of DNA damage response markers were also diminished by co-treatment. Collectively, our results reveal a novel mechanism by which capsaicin sensitizes oral cancer cells to anticancer drugs through the up-regulation of autophagy and down-regulation of ribophorin II, and further indicate that the induction of necroptosis is a critical factor in the capsaicin-mediated chemosensitization of oral squamous carcinoma cells to conventional anticancer drugs.